Multi-output Portable Universal Power Supply Kit with Plug-and-Use Equipment for Emergency Application - A. Nazifah Abdullah; M. Asri Jusoh; Norkharziana Mohd Nayan; M. Syahril; N. Nadiah Ayop (Institute of Advanced Engineering and Science, 2017)
This paper presents design and analysis of Multi-output Portable Universal Power Supply Kit (EPS Kit). This EPS Kit is intended as an alternative power supply kit to reduce the issue of a power outage. Lead Acid Battery which is considered one of the easiest sources that can be found during an emergency state is the best alternative energy source. The EPS Kit is designed to store the power in Lead Acid Battery as the main source and powered by the solar energy as the secondary source and will be providing both standard household alternating current (AC) and most common direct current (DC) power. This Kit is a stand-alone system comes with plug-and-use kit in which the system can be recharged using solar and AC power. The plug-and-use kit is equipped with intelligent multi-USB ports, adjustable dual mode NiCd, Ni-Mh, and Li-Ion battery which are Discharge/Charger mode, AC output port, LED lamp, and emergency electrical accessories. EPS Kit is also portable which installed with wheel and handle for mobility application. Production of EPS Kit is involved software and hardware. The software used are 3D CAD design software and circuit simulation software respectively for preliminary 3D drawing design and output circuit validation. Experimental results of the EPS Kit load testing, charging and discharging state are conducted in order to demonstrate the EPS Kit functionality and usage.